Sepsis-induced acute kidney injury in oral and maxillofacial infection with upper airway obstruction due to retropharyngeal abscess a case report - Irsan Kurniawan; Agus Nurwiadh; Kiki Lukman (DiscoverSys Inc., 2016)
Left untreated or not properly managed odontogenic infection can cause spreading into facial spaces. Severe oral and maxillofacial infection can spread systemically and cause sepsis.1 Sepsis can induce unfavorable condition for the kidney, which is Acute Kidney Injury (AKI).2,3 The aim of this paper is to report a rare case of an oral and maxillofacial infection with sepsis-induced AKI and upper airway obstruction which have high mortality rate. The standard treatment consists of proper monitoring of vital function, fluid resuscitation, drainage of accumulated purulence, empirical use of antibiotics chosen to cover the spectrum of potential pathogens until culture results are available, and supplemental oxygen.1,4 This is a case report of a 48 year old female patient with oral and maxillofacial infection suffers sepsis-induced AKI and upper airway obstruction. This patient was diagnosed as right submandibular abscess which has extended into right buccal space, with sepsis, stage I AKI, and upper airway obstruction due to retropharyngeal abscess. We managed this patient with oxygenation, fluid resuscitation, antibiotics and analgesic administration, incision and drainage, and also extraction of mandibular right third molar. Tracheostomy, incision and drainage of retropharyngeal abscess were supposed to be performed by ENT department, but the patient refused. However the patient still survived. In case of oral and maxillofacial infection, the involvement of distant organ should be investigated, because this conditions result in high mortality rate. Early diagnosis and prompt treatment are important and able to lead to a better survival.